Analisis Pengaruh ROA, CAR, NPL Dan LDR Terhadap Pemberian Kredit Sektor Perbankan - Ratnawati, Ratnawati (Arthavidya Jurnal Ilmiah Ekonomi, 2014)
Business competition is getting tougher demands banksto improve their performance in order to attract investors.Investors invest funds require prior information about thecompany's performance. Objects in this study is a manufacturingcompany in Indonesia Stock Exchange. IDX is considered torepresent the Indonesian capital market, so that the findings in thisstudy are considered as the findings of the case in Indonesia . Thepopulation in this study is a banking company that is listed on theIndonesia Stock Exchange ( IDX ) in the period of study (2010-2012) . Based on these criteria, the number of samples used in thisstudy were 10 banking companies. Based on the results ofstatistical analysis and discussion of the Return On Assets ( ROA )has a positive and significant impact on bank lending in the tenlargest banks listed on the Stock Exchange. Non Performing Loans(NPL) and Loan to Deposit Ratio (LDR) has a negative andsignificant effect on bank lending in the ten largest banks listed onthe Stock Exchange. Capital Adequacy Ratio (CAR) had nosignificant effect on bank lending in the ten largest banks listed onthe Stock Exchange .Keyword: Return On Assets (ROA), Capital Adequacy Ratio(CAR), Non Performing Loans (NPL), Loan to Deposit Ratio(LDR), Bank Lending.